Biological correlates of self-reported new and continued abstinence in cannabis cessation treatment clinical trials - Baker, Nathaniel L. (Drug Alcohol Depend, 2018)
BACKGROUND: The agreement between self-reported cannabis abstinence with urine cannabinoid concentrations in a clinical trials setting is not well characterized. We assessed the agreement between various cannabinoid cutoffs and self-reported abstinence across three clinical trials, one including contingency management for abstinence. METHODS: Three cannabis cessation clinical trials where participants reported use and provided weekly urine samples for cannabis and creatinine concentration measurements were included. Bootstrapped data were assessed for agreement between self-reported 7+ day abstinence and urine cannabinoid tests using generalized linear mixed effects models for clustered binary outcomes. One study implemented contingency management for cannabis abstinence. Four hundred and seventy-three participants with 3787 valid urine specimens were included. Urine was analyzed for 11-nor-9-carboxy-Δ9-tetrahydrocannabinol and creatinine using immunoassay methods. Biological cutoffs of 50, 100, and 200 ng/ml, as well as changes in CN normalized THCCOOH (25%/50% decrease), were assessed for agreement with self-reported abstinence during the three clinical trials. RESULTS: Agreement between measured THCCOOH and self-reported abstinence increases with increasing cutoff concentrations, while the agreement with self-reported non-abstinence decreases with increasing cutoff concentrations. Combining THCCOOH cutoffs with recent changes in CN-THCCOOH provides a better agreement in those self-reporting abstinence. Participants in the studies that received CM for abstinence had a lower agreement between self-reported abstinence and returned to use than those in studies that did not have a contingency management component. CONCLUSION: Using combinations of biological measurements and self-reported abstinence, confirmation of study related abstinence may be verifiable earlier and with greater accuracy than relying on a single measurement.